FAKTOR YANG MENENTUKAN MINAT BELI KONSUMEN J.CO DONUTS - Albertus Maria Setyastanto (Journal Of Communication Education, 2016)
Abstract Each company will take into account the right strategy to create the product. The product must be able to attract consumers to buy. To be able to formulate appropriate strategies in creating a product is not easy because it takes an understanding of the products that fit the needs and desires of consumers. This research aims to determine any factors that make consumers interested in buying a product J.CO Donuts. Data were collected by distributing 100 questionnaires in Bekasi, in January 2015. In order to analyze the data used Multiple Regression calculation. Based on the results of the study, the authors obtained four factors obtained from the reduction and the results of these four factors, there are three dominant factors that determine interest in buying products J.CO Donuts, namely: product, prices, and place.  Key words: Product, Prices, Place, Promotion, interest in buying Abstrak Setiap perusahaan akan memperhitungkan strategi yang tepat untuk menciptakan produk. Produk tersebut harus mampu menarik minat para konsumen untuk membelinya. Untuk dapat merumuskan strategi yang tepat dalam menciptakan produk tidaklah mudah karena dibutuhkan pemahaman akan produk yang sesuai dengan kebutuhan dan keinginan para konsumen. Penelitian yang dilakukan ini bertujuan untuk mengetahui faktor-faktor apa saja yang membuat konsumen berminat untuk membeli produk J.CO Donuts. Data dikumpulkan dengan menyebarkan 100 kuesioner di wilayah Bekasi, pada bulan Januari 2015. Untuk menganalisis data digunakan perhitungan Regresi Ganda. Berdasarkan hasil penelitian, penulis memperoleh empat faktor yang didapatkan dari hasil reduksi dan dari hasil empat faktor tersebut terdapat tiga faktor dominan yang menentukan minat beli ulang produk J.CO Donuts, yaitu: produk, harga, dan tempat. Kata kunci: Produk, Harga, Tempat, Promosi, Minat beli